Geothermal energy production potential of karst geothermal reservoir considering mining-induced stress - Jinghong Yan; Dan Ma; Xuefeng Gao; Hongyu Duan; Qiang Li; Wentao Hou (International Journal of Mining Science and Technology)
Developing hydrothermal resources in highly conductive karst aquifers at deep mine floors is regarded as a potential approach to achieving the co-development of coal and geothermal resources. However, the heat transfer potential of the fracture system in the target reservoir under mining activities remains in suspense. Hence, a coupled thermal–hydraulic-mechanical model was developed for the karst reservoir of Anju coal mine in China, considering non-isothermal convective heat transfer in fractures. This model examined the influence of stress redistribution due to different mining distances (MD) on the effective flow channel length/density and the high/low-aperture fracture distribution. The dynamic heat generation characteristics of the geothermal reservoir were evaluated. Key findings include: Mining-induced stress creates interlaced high-aperture and low-aperture fracture zones below the goaf. Within these interlaced zones, the combined effect of high- and low-aperture fractures restricts the effective flow channel length/density of the fracture network. This contraction of the flow field leads to a significant decline in production flow rate, which consequently reduces both the production flow rate and power as MD increases. This work represents the study of mining disturbances on geothermal production, providing a theoretical foundation for the co-development of coal and geothermal resources.